"The Origins of Interpretation and its Mechanisms: Between Heritage Concepts and Modernity’s Contributions – Temptations and Pitfalls". - belkheir.refice, belkheir.refice (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(–header-height)" dir="auto" data-turn-id="2f1f8989-083f-456f-a1de-623cad4cee60" data-testid="conversation-turn-33" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:d400b35d-1010-4ff5-921c-c9cfc9a31924-16" data-testid="conversation-turn-34" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="5f695633-131c-499d-b5b8-17fb351fa7ba" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> "This paper derives its perspective from the intellectual concern that has continuously haunted the traditional intellectual system, urging it to comply with epistemological concepts and propositions, and compelling it to acknowledge the necessity of adopting mechanisms that respond to the requirements of the text as a product, irrespective of the particularities it carries or the sanctity that surrounds i